2020
DOI: 10.5009/gnl18575
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Metachronous Gastric Cancer after Endoscopic Resection for Early Gastric Cancer

Abstract: Background/Aims: Patients treated with endoscopic submucosal dissection (ESD) for early gastric cancer (EGC) are at risk of developing metachronous gastric cancer (MGC). The aim of this study was to evaluate the clinical outcomes of MGC after ESD for EGC between the re-ESD and surgery groups. Methods: In total, data from 1,510 patients who underwent ESD for EGC from January 2005 to May 2014 were retrospectively reviewed, and data from 112 patients with MGC were analyzed according to the type of treatment, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
(34 reference statements)
0
6
0
1
Order By: Relevance
“…It was demonstrated that high BMI (≥25 kg/m 2 ) increased the risk of EGC or mucosal dysplasia (36), with insulin resistance playing an important role (37). But other studies showed that lower BMI was associated with metachronous GC (38) and worse survival of EGC patients (39). Our analysis identified BMI as a protective factor of both LNM and LVI in EGC-UDC, which was consistent with previous findings that BMI was inversely associated with tumor size, tumor depth, LNM and tumor stage in early or advanced GC (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that high BMI (≥25 kg/m 2 ) increased the risk of EGC or mucosal dysplasia (36), with insulin resistance playing an important role (37). But other studies showed that lower BMI was associated with metachronous GC (38) and worse survival of EGC patients (39). Our analysis identified BMI as a protective factor of both LNM and LVI in EGC-UDC, which was consistent with previous findings that BMI was inversely associated with tumor size, tumor depth, LNM and tumor stage in early or advanced GC (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Through a literature review, we found only one previous study; it reported body mass index (BMI) and the multiplicity of initial gastric cancers as independent predictors. 15 Therefore, based on this study and our clinical knowledge, we chose nine possible confounders: age, sex, BMI, smoking, American Society of Anesthesiologists physical status, the degree of gastric mucosal atrophy, persistent H. pylori infection, the multiplicity of initial gastric cancers, and the curability of the first ESD. The PS models were then used to match the short-and regularinterval groups at a 1:2 ratio within a caliper width of 0.2 using a greedy nearest-neighbor algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…При выборе данной хирургической методики желудок сохраняет свою функцию, существенно не страдает качество жизни пациента [38]. Недостатком резекции желудка является риск развития МРЖ в нерезецированной части органа, частота которого составляет 2,7-15,6 % [36,39,40]. Основными факторами риска данного процесса являются пожилой возраст, неоднократный ранний рак желудка в анамнезе, а также персистенция H. pylori [39].…”
Section: рак желудкаunclassified